A one-year-long aerobic incubation experiment assessing CO? and CH? production in thermokarst terrain on the Barrow Peninsula, Arctic Alaska - Fabian Seemann; Mackenzie Baysinger; Susanne Liebner; Maren Jenrich; Guido Grosse; Benjamin Jones; Claire C Treat; Jens Strauss (PANGAEA, 2025)
During an expedition in April 2022, four sediment cores were taken from thermokarst terrain on the Barrow Peninsula (Alaska). In the subsequent laboratory experiment, wet sediment samples (15 g) were incubated for 382 days under aerobic conditions at 10 °C. Along the undisturbed tundra upland core, one sample was taken from the active layer and two samples from the permafrost domain. Since a short core from the talik was retrieved from West Twin Lake, one sample was chosen from this core. The East Twin Lake core was characterized by unfrozen cryotic conditions (cryopeg), from which three samples were selected along the core. From the drained lake basin core, two samples were taken from the active layer and one from the permafrost domain. Each of the ten incubation samples was divided into three replicates, resulting in a total of 30 samples. At day 0 of the experiment, all vials were flushed with synthetic air (20 % O2, 80 % N2). CO2 and CH4 concentrations were measured three times per week during the first two weeks, two times per week from week 3 to 7, one time per week from week 8 to 15, and at regular two-week intervals thereafter until day 382 (week 56). Measurements were conducted with a gas chromatograph (7890A, Agilent Technologies, USA). If CO2 concentrations exceeded 10,000 ppm, the vial extquotesingles headspace was immediately flushed with synthetic air for three minutes and re-measured afterwards. Raw data were processed following Baysinger and Dolle (2025).